Ex vivo depletion of T cells from bone marrow grafts with CAMPATH-1 in acute leukemia: graft-versus-host disease and graft-versus-leukemia effect. - Novitzky, N; Thomas, V; Hale, G; Waldmann, H (1999)
BACKGROUND: Preventing graft-versus-host disease (GVHD) by depletion of T lymphocytes from the stem cell graft for transplantation remains controversial, mainly because of the perceived increase in disease recurrence. METHODS: We retrospectively analyzed the outcome of 50 consecutive individuals in remission of acute lymphoblastic leukemia (n=13; 8 in complete remission [CR]1) or acute myeloblastic leukemia (n=37; 33 in CR1), who had received marrow grafts from HLA-identical siblings. The conditioning regimen included six 2-Gy fractions of total body irradiation, succeeded by cyclophosphamide at 120 mg/kg (with mesna) followed by four fractions of 1.5 Gy to lymphoid areas. Bone marrow (n=38) or peripheral blood mobilized donor mononuclear cells (n=12) were exposed ex vivo to CAMPATH-1 (IgM and complement, or IgG; antiCD52) antibodies, without any further posttransplantation immunosuppression. RESULTS: Median patient age was 31 (range 14-51) years; 12 patients were 40 or older. Thirty-two patients were male. One patient died of pulmonary hemorrhage on day 10; another died on day 29 of interstitial pneumonitis. Except for one early death, all patients engrafted. Ten (21%) of the remaining 48 who were at risk, developed GVHD. In none was it greater than grade II. Eight patients developed serious viral infections. Four died of cytomegalovirus pneumonia, adenovirus hepatitis, and human immunodeficiency. Overall, 11 patients (22%) relapsed (4 of 33 acute myeloblastic leukemia in CR1) at a median of 235 (range 46-528) days. Mean posttransplantation follow-up was 1062 (median 560; range 10-4177) days. Thirty-three patients (66%) remained disease free at a mean of 1,118 (median 1439; range 159-4,177) days. For all patients, the performance status was between 82% and 100% (median 100). CONCLUSION: T-cell depletion with CAMPATH-1 effectively prevents GVHD, particularly the severe acute forms, without leading to excessive risk of relapse in acute leukemia.